Slum Management In Bekasi: : Current Trends And Ways To Improve - Tariq Al-Sindi; Khairil Asnan Haedar; Dahyar Daraba (International Journal of Educational Administration, Management, and Leadership, 2023)
This study investigates current trends in Bekasi, Indonesia, slum management policy, and recommends solutions to improve living standards among slum dwellers. Slums are a major issue in metropolitan city as Bekasi that has several obstacles in meeting slum folk’s needs while supporting sustainable urban growth. This research evaluates existing policies and their consequences using interview data, detects developing patterns using GIS-based approach, and offers innovative measures to improve slum management in Bekasi. To address the multifaceted issues, we applied management strategy by Wheleen Hunger that consists of strategic analysis, formulation, and implementation and combined with sustainability framework incorporates social, economic, and environment point of view of slum management. The findings emphasize the significance of a holistic and inclusive approach that integrates social, economic, and environmental components.